2020
DOI: 10.1007/s00520-020-05403-2
|View full text |Cite
|
Sign up to set email alerts
|

Medical cannabis in supportive cancer care: lessons from Canada

Abstract: Medical cannabis, or cannabinoid-based products, continues to grow in popularity globally, driving the evolution of regulatory access frameworks; cancer patients and caregivers often rely on guidance from their physicians regarding cannabinoid-based treatments. But the majority of healthcare practitioners still feel unprepared and insufficiently informed to make reasonable, evidence-based recommendations about medical cannabis. More than 30 countries worldwide have now legalized access to medical cannabis; yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The role of Cannabis sativa in medicine is rapidly evolving. More than 30 countries worldwide have now legalized access to medical use of Cannabis [ 146 , 147 ]. A prospective observational study showed that many cancer-related symptoms improve significantly with Cannabis consumption.…”
Section: Cannabis Sativa L In Cancer Clinical Trialsmentioning
confidence: 99%
“…The role of Cannabis sativa in medicine is rapidly evolving. More than 30 countries worldwide have now legalized access to medical use of Cannabis [ 146 , 147 ]. A prospective observational study showed that many cancer-related symptoms improve significantly with Cannabis consumption.…”
Section: Cannabis Sativa L In Cancer Clinical Trialsmentioning
confidence: 99%
“…Although cannabis has been used for thousands of years to treat diverse medical conditions and symptoms 10 , its clinical use, research, and development have been hindered by global prohibition throughout the last century. Significant barriers remain, including variable and complex regulatory restrictions, paucity of high-quality clinical evidence and limitations on research development, social stigma, and limited medical cannabis academic training of health-care professionals 11 . At present, < 13% of patients with gastrointestinal disorders consult with their physician about proper cannabinoid prescription and optimal medical guidance 12 .…”
Section: Why Medical Cannabis?mentioning
confidence: 99%
“…Naftali et al 2011 [13] Retrospective observational study/Israel 30 patients (26 men and 4 women; 21-65 y) with CD using cannabis (because of lack of response to conventional therapy) were interviewed. Four patients used recreational cannabis.…”
Section: Not Reportedmentioning
confidence: 99%
“…It is also worth remembering that the use of CS still leads to numerous questions about effectiveness and safety, making healthcare professionals still very concerned about the adverse effects such as psychotropic side effects, increase food intake, short-term memory, and other cognitive deficits [13,51].…”
Section: Cannabis Sativa and Endocannabinoid Systemmentioning
confidence: 99%
See 1 more Smart Citation